Mobilising adaptive capacity to multiple stressors: Insights from small-scale coastal fisheries in the Western Region of Ghana. Issue 91 (May 2018) - Freduah, George; Fidelman, Pedro; Smith, Timothy F.
Highlights: Mobilising adaptive capacity involves a complex interaction among "main-available" and "supporting-available" capitals. A strategic way to enhance adaptive capacity is to develop the "main-available" capitals. "Main-available" capitals are mobilised and used in response to stressors as a matter of need rather than choice. Abstract: The processes by which adaptive capacity is mobilised in response to multiple stressors are yet to be fully understood. This study addresses this pressing research gap by drawing on the capitals framework and empirical data from small-scale coastal fisheries in the Western Region of Ghana. It employs an ethnographic approach, based on multiple sources of evidence including documents, interviews and participant observation to examine mechanisms of mobilising adaptive capacity in response to climate and non-climate stressors. Our findings suggest that responding to stressors involves mobilising sets of main-available capitals, such as local innovation, ability to improvise, new technologies, corrupt practices and belief systems (cultural capital); collective action, networks and social ties (social capital); and complaints to the government (political capital). These capitals were the main constituents of adaptive capacity, particularly considering non-responsive government and formal organisations. Further, other forms of capitals, i.e., local leadership, local knowledge, learning capacity, and training (human capital); networks, collective actions, associations and bonding ties (social capital); sand (natural capital); funds from fishing (financial capital), combine in complex ways to mobilise such available capitals. This understanding is critical if synergies among main-available and supporting-available capitals are to support building and mobilizing adaptive capacity. Further, it may help guide important decisions, proactive plans and strategic investment for developing key capitals to enhance adaptive capacity.